Generation of benzyne from aryl benziodoxaborole triflate under aqueous conditions and its reactions with alkyl aryl sulfides; Arkivoc; Vol. 1 - Yoshimura A. Akira; Ngo Kim; Mironova I. A. Irina Andreevna; Gardner S. Zachary; Ogura Nami; Ueki Akiharu; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Saito Akio; Zhdankin V. V. Viktor Vladimirovich (2024, 2024)
Title screen